Echo Boomers’ Job Hopping Behavior: Moderating Role of Emotional Intelligence on Burnout and Career Growth - Nursanti, Tinjung Desy; Salsabila DF, Dhiya (STIE Indonesia Banking School, 2025)
The generation of the